The difference of sweet taste threshold before and after using mouthwash containing zinc sulfate - Janarikamain, Agung Ayu Dewi; Haroen, Edeh Roletta; Dardjan, Murnisari (Universitas Padjadjaran, 2010)
Introduction: Mouthwash containing zinc sulfate could reduce the ability of tasting sweetness temporarily. Zinc sulfate is an example of a zinc compound which is the active ingredient in mouthwash. Zinc sulfate is added in mouthwash as an antiplaque and astringent material that gives a cleaning on the mouth. This study aimed is to analized differences of sweet taste threshold changes data before and after using mouthwash containing zinc sulfate. Methods: The study was using quasi experimental study. Study sample was collage students of Dentistry Faculty of Padjadjaran University totally 30 sample ages between 18-25 years old men and women took based on purposive sampling. Murphy method was applied to measure the threshold of sweet taste perception and identification before and after using mouthwash containing zinc sulfate. Results: The result of statistically shows the average value of sweet perception threshold before and after using mouthwash containing zinc sulfate are 0.0046 M and 0.0128 M with standard deviation 0.0047 and 0.0084. Sweet identification threshold before and after using mouthwash containing zinc sulfate are 0.0164 M and 0.0248 M with standard deviation 0.0089 and 0.0082. Conclusion: There is difference of sweet taste threshold before and after using mouthwash containing zinc sulfate.